The Effect of Organizational Justice and Job Embeddedness on Turnover Intention in Textile Sector of Pakistan: The Mediating Role of Work Engagement - Amin, Muhammad; Othman, Siti Zubaidah; Saoula, Oussama (CENTRAL ASIA AND THE CAUCASUS, 2021)
This study aims to examine the effect of organizational justice (OJ) and job embeddedness (JE) on Turnover intention (TI). Also, the study intends to investigate the role of work engagement (WENG) as a mediating factor in the effect of OJ and JE on TI. A self -administered survey was used to collect data from 384 employees working in the textile industry of Pakistan. The data was analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings of the study showed a statistically significant relationship between the key study variables. The WENG was discovered to partially mediates the relationship between OJ, JE, and TI. The result suggests that the organizations can proactively improve both work engagement and employees’ retention through organizational justice and job embeddedness. The research contributes to the existing literature of the key study variables.